Multiple myeloma with hepatic amyloid light-chain amyloidosis manifesting as progressive liver failure - Oye, Monique (BMJ Case Rep, 2020)
We present a case of a 45-year-old man admitted to the hospital with new-onset ascites and bilateral subconjunctival haemorrhages. He was found to have elevated liver enzymes in a hepatocellular pattern and direct hyperbilirubinemia. A diagnostic paracentesis was consistent with portal hypertension (PH). Extensive workup for acute and chronic liver disease was unremarkable. In the absence of clinical evidence of cirrhosis to explain PH, a liver biopsy with hepatic venous pressure gradient was pursued, which revealed proteinaceous material and apple-green birefringence under polarised light consistent with amyloid deposits. Bone marrow biopsy revealed plasma cell neoplasm with proteinaceous deposits consistent with concomitant multiple myeloma with AL amyloidosis. He developed rapidly progressive liver failure and passed shortly after presentation despite treatment with chemotherapy. This case illustrates how primary hepatic amyloidosis can present with a physiology that mimics cirrhosis and can easily be missed.